1968
DOI: 10.1017/s0033583500000445
|View full text |Cite
|
Sign up to set email alerts
|

New looks and outlooks on physical enzymology

Abstract: Our scientific age is characterized by the extension of our dimensions to the extreme. Radiotelescopes are searching for echoes from the depth of the universe, while electronmicroscopes and X-ray diffractometers make the atomic and molecular structure of matter visible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 12 publications
(15 reference statements)
4
96
0
Order By: Relevance
“…In the tumble frequency assay, the rate of generation of attractant is too rapid to be rate-limiting and, unlike in shallow gradient conditions, the level of X is not an integrated result of stimuli in a changing environment. This system yields a response independent of rate of delivery of the stimulus and, therefore, the recovery curves measure the relaxation to normal in much the same way as temperature jump relaxation curves (20). A conclusion from our experiments is that the total number of tumbles suppressed, when measured over a period of time that encompasses all effects of the stimulus, would depend only on the amount of chemoreceptor occupancy change.$ The ability of the assay to achieve this separation of the stimulus-response relationship provides a tool for the analytical evaluation of the tumble regulator role.…”
Section: Discussionmentioning
confidence: 99%
“…In the tumble frequency assay, the rate of generation of attractant is too rapid to be rate-limiting and, unlike in shallow gradient conditions, the level of X is not an integrated result of stimuli in a changing environment. This system yields a response independent of rate of delivery of the stimulus and, therefore, the recovery curves measure the relaxation to normal in much the same way as temperature jump relaxation curves (20). A conclusion from our experiments is that the total number of tumbles suppressed, when measured over a period of time that encompasses all effects of the stimulus, would depend only on the amount of chemoreceptor occupancy change.$ The ability of the assay to achieve this separation of the stimulus-response relationship provides a tool for the analytical evaluation of the tumble regulator role.…”
Section: Discussionmentioning
confidence: 99%
“…The former mechanism defines pre-equilibrium (41) and depicts a macromolecule existing in two possible conformations, from which the ligand selects only one, i.e. Scheme 2.…”
Section: Methodsmentioning
confidence: 99%
“…For scheme IV, Eigen (1968) has shown that the sums and products of the reciprocal relaxation times are given by: 25) and in favorable cases these two combinations can be plotted versus ([P]+[L]) to yield all four rate constants (Eigen, 1968). If the relaxation times are sufficiently well separated, these equations can be uncoupled to relate the individual relaxation times to particular steps.…”
Section: Relaxation Methodsmentioning
confidence: 99%